If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 + -2b = b + 4 Reorder the terms: -17 + -2b = 4 + b Solving -17 + -2b = 4 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -17 + -2b + -1b = 4 + b + -1b Combine like terms: -2b + -1b = -3b -17 + -3b = 4 + b + -1b Combine like terms: b + -1b = 0 -17 + -3b = 4 + 0 -17 + -3b = 4 Add '17' to each side of the equation. -17 + 17 + -3b = 4 + 17 Combine like terms: -17 + 17 = 0 0 + -3b = 4 + 17 -3b = 4 + 17 Combine like terms: 4 + 17 = 21 -3b = 21 Divide each side by '-3'. b = -7 Simplifying b = -7
| 12x+2=40 | | 10=-3x-5 | | 13x=39 | | 2=-5+3b+4b | | 3(b+7)=30 | | 2d+3=11 | | 5x+20=3x+30 | | 2x-13=9+4x | | 2x-1=4x-5 | | -6+17= | | 5=-40-9p | | 7=t-(-7) | | 48=12d | | Y-4=1 | | 8m^2-4m-2=0 | | 0=7p-35 | | 4(x-3)-8=16 | | 15f-8f+13= | | 2x-37=-15 | | 8-2u=12 | | -3x-3=-36 | | T+9=20 | | 5n-8=12 | | 5a=24-3a | | 3-2(x+3)=x-18 | | 5+m=8 | | (3x+1)(x-4)=0 | | 6x-2x-9= | | 5x-3=18+2x | | -10x=-100 | | 18x^2+12x+2=0 | | x+y+z=2 |